Partial Invasive Mole with Bilateral Torsion of Theca Lutein Cysts - Yadav, Randhir Sagar; Shrestha, Shumneva; Sharma, Santosh; Singh, Meeta; Bista, Kesang Diki; Ojha, Neebha (Journal of Nepal Health Research Council, 2018)
Gestational trophoblastic neoplasia is extremely rare entity accounting 1% of all gynecological malignancies. Invasive mole is a form of Gestational trophoblastic neoplasia which is locally invasive with propensity of metastasis. Association of partial mole with invasive mole and/or theca lutein cysts is a rare occurrence. Large cysts may present with complications. A case with these rare combinations presented at 15+3 weeks period of gestation as acute abdomen due to torsion of bilateral theca lutein cysts is reported. Right salpingo-ophorectomy with untwisting of left cyst was done. Six cycles of chemotherapy was given with regular Î²hCG monitoring. First trimester dating scan would have helped in early diagnosis, treatment and prevention of complications. Keywords: Invasive mole; theca lutein cysts; torsion.